Fluorescence Detection of Anilines and Photocatalytic Degradation of Rhodamine B by a Multifunctional Metal–Organic Framework. Issue 36 (25th November 2014) - Wang, Fengqin; Dong, Caifu; Wang, Zechuan; Cui, Yaru; Wang, Chengmiao; Zhao, Yongnan; Li, Guodong
Abstract: A multifunctional transition metal Cd II coordination polymer based on an amide‐inserted flexible multicarboxylate ligand, bis(3, 5‐dicarboxyphenyl)terephthalamide (H4 L), [CdL]· [ + H2 N(CH3 )2 ] (DMF)(H2 O)3 (MOF1) was synthesized by the solvothermal method. Its structure was determined by single‐crystal X‐ray diffraction analysis and it was characterized by elemental analysis, IR spectroscopy and thermogravimetric analysis. MOF1 shows selective sensitivity to detecting aniline pollutants in both aqueous media and as vapors due to its strong fluorescence emission and microporous structure. In addition, the visible‐light‐driven photocatalytic degradation of Rhodamine B (RhB) by MOF1 and polyaniline (PANI) composite material (named PANI/MOF1), which was prepared by loading PANI onto the surface of MOF1, was also studied. The results obtained illustrate that PANI/MOF1 exhibits improved photocatalytic activity over MOF1, which could be used to effectively treat wastewater containing organic dyes in the future. Abstract : A multifunctional metal–organic framework for determination of toxic aromatic amines has been constructed and it shows photocatalytic degradation of organic dyes due to the combination of luminescence and accessible porosity within the MOF.